Polyconjugated Materials for Printed (Opto)Electronics: Introducing Sustainability - Sassi, Mauro; Mattiello, Sara; Fappani, Alice; Beverina, Luca (Synlett, 2023)
This account summarizes the impact that the quest for sustainability is having on the field of organic polyconjugate molecules and polymers for plastic (opto)electronics. While at the proof-of-concept level, the design criteria as well as the preferred synthetic strategies to access new and improved materials have been dominated by the need for performance. The ongoing transition from the lab environment to the industrial scale imposes strict limitations on the cost and overall environmental impact of new materials. We here summarize our efforts on the development of new design criteria and synthetic strategies aimed at improving sustainability – without compromising performance – in organic polyconjugated molecules. The article is composed of three sections: Introduction and motivation, sustainability through improved synthetic methods and through improved design.Outline1 Introduction and Motivation2 Sustainable Reaction Methods2.1 The New Tools: Reactions in Aqueous Solution of Surfactants2.2 Intrinsically More Sustainable Reactions: Direct Arylation2.3 Sustainable Multistep Protocols: Combining Micellar, Solventless, and Mechanochemical Methods3 Sustainability as a Design Criterion: De Novo Design4 Conclusion
Keywords: organic semiconductors; micellar catalysis; sustainability; association colloids; E-factor